Calcium in shell, seed coat, and seed in relation to resistance of peanut genotypes to Aspergillus flavus infection - Prachan Janpengphat (2018)
Infection of peanut (Arachis hypogaea L.) by Aspergillus flavus and subsequent aflatoxin contamination is a serious health and economic concern worldwide. Considering the role of calcium (Ca) in cell wall development, it has been shown to be associated with reduced A. flavus infection. In order to examine the influence of Ca content in shell (also called pod wall or hull), seed coat, and seed in relation to resistance to A. flavus infection, a pot experiment was conducted in a greenhouse of the Faculty of Agriculture, Chiang Mai University, Thailand during May-September, 2006, using three peanut genotypes: 419CC, drought and aflatoxin susceptible; 511CC, drought and aflatoxin resistant; and Tainan 9, a commercial variety in Thailand. Results showed that an increase in the concentration of Ca in the nutrient solution increased in the amount of Ca in shell, seed coat, and seed, and that higher Ca content was reduced the incidence of shell and seed infection by A. flavus for all three peanut genotypes. Genotype 511CC had the highest Ca content in shell (0.35 g/100 g), seed coat (0.37 g/100 g) and seed (0.40 g/100 g) and had the lowest incidence of A. flavus infection in shell (8.1%) and seed (2.2%) as compared to genotype 419CC, which had the lowest Ca content in shell (0.21 g/100 g), seed coat (0.18 g/100 g), and seed (0.20 g/100 g) and had the highest infection of shell (36.3%) and seed (13.3%). No seed infection was found in genotype 511CC under a high concentration of Ca (2500 ppm). From these results, it could be suggested that Ca content in peanut shell, seed coat, and seed might be applied as a criterion in selection for resistance to A. flavus infection. It was also found that genotype 511CC supported the lowest levels of A. flavus infection which suggested that this genotype might be a potential source of resistance that could be used to incorporate aflatoxin resistance into commercial peanut hybrids.